A comparative study on thermal performance evaluation of a new double skin façade system integrated with photovoltaic blinds. (1st August 2017) - Luo, Yongqiang; Zhang, Ling; Wang, Xiliang; Xie, Lei; Liu, Zhongbing; Wu, Jing; Zhang, Yelin; He, Xihua
Highlights: A new double skin façade using photovoltaic blinds was proposed and studied. Experiment and simulation method were used for comparative study. Influence of different system ventilation modes and blind parameters were analyzed. Thermal performance of proposed façade and standard double skin façade was compared. Abstract: The glazing façade is embraced by architects, but this configuration may result in huge energy consumption. This research proposed a new double skin façade using photovoltaic (PV) blinds as a shading device (named PVB-DSF), which could realize multi-function of power generation, solar penetration reduction and flexible daylighting control. The purpose of this comparative study is to demonstrate the superb thermal performance of PVB-DSF. Experimental rig was built at hot-summer and cold-winter zone of China. The first stage comparative study was conducted to evaluate system thermal performance under the effects of ventilation modes, PV-blind angle and PV-blind spacing. The second stage study was conducted to compare thermal performance between PVB-DSF and standard DSF. A validated numerical model was used to describe standard DSF. The results suggested the operation of natural ventilation mode and indicated the evident influence of PV-blind spacing on system performance. The comparison study further demonstrated that PVB-DSF can save about 12.16% and 25.57% of energy in summer compared with conventional DSF with and without shading blinds. The insulation performance of PVB-DSF is shown by its daily average heat transfer coefficient which was as low as 2.247.